Examining the impact of Omani primary school climate and teacher self-efficacy on innovative teaching practices: a structural equation modeling approach - Alshuhumi, Said; Al-Hidabi, Dawood; Aldaba, Abdulmajid; Ateeq, Ali; Almuraqab, Nasser; Ibrahim, Siddig; Al-refaei, Abd Al-Aziz (Frontiers in Education, 2025)
PurposeThe main objective of this research is to examine the influence of Omani school organizational climate and teachers’ self-efficacy on their innovative teaching practices. Moreover, the current study aimed to test the mediating role of teachers’ self-efficacy in the relationship between the two constructs.Research methodThis study employed the cross-sectional survey method to collect data from 368 primary school teachers in Muscat employing the simple random sampling procedure. Structural equation modeling (SEM) through AMOS was utilized in two main steps: measurement model and structural model to analyze the study data.FindingsThe findings revealed a statistically significant influence of Omani school organizational climate and teachers’ self-efficacy on their innovative behavior. Moreover, teachers’ self-efficacy was found to mediate the relationship between the two variables.ImplicationsThese outcomes provide valuable insights for policymakers, urging them to consider the dimensions of school climate and teachers’ self-efficacy. Such considerations can yield positive effects on the enhancement of teachers’ innovative behavior, thereby improving the overall learning process.OriginalityIn light of these findings, the study suggests that fostering the development of school climate and teachers’ self-efficacy should be encouraged to promote innovative behavior within Omani primary schools.